2020
DOI: 10.1002/mds.28322
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Study of Opicapone in Japanese Parkinson's Patients with Motor Fluctuations

Abstract: Objectives This placebo‐controlled, randomized study evaluated the efficacy and safety of opicapone 25‐mg and 50‐mg tablets in Japanese levodopa‐treated patients with Parkinson's disease and motor fluctuations. Methods Japanese adults (n = 437, age 39–83 years) with Parkinson's disease (United Kingdom Parkinson's Disease Society criteria) received opicapone 25‐mg (n = 145), opicapone 50‐mg (n = 145), or placebo (n = 147) tablets over the double‐blind treatment period (14–15 weeks). The primary efficacy assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
4
22
0
Order By: Relevance
“… 40 Overall, the efficacy results in this study are broadly consistent with those seen in BIPARK I and II, however the least squares mean changes in OFF-time were numerically lower in Japanese patients than in the BIPARK I and II studies for OPC 25 mg, 50 mg, and placebo. 26 , 40 …”
Section: Opicapone Lifecycle: From Conception To Commercializationsupporting
confidence: 81%
See 2 more Smart Citations
“… 40 Overall, the efficacy results in this study are broadly consistent with those seen in BIPARK I and II, however the least squares mean changes in OFF-time were numerically lower in Japanese patients than in the BIPARK I and II studies for OPC 25 mg, 50 mg, and placebo. 26 , 40 …”
Section: Opicapone Lifecycle: From Conception To Commercializationsupporting
confidence: 81%
“… 40 The main conclusion of this study is that once-daily adjunct OPC tablets at doses of 25 and 50 mg significantly reduced OFF-time compared with placebo among Japanese L-Dopa treated patients with PD and motor fluctuations, with no dose dependency between OPC tablet dosages. 40 Overall, the efficacy results in this study are broadly consistent with those seen in BIPARK I and II, however the least squares mean changes in OFF-time were numerically lower in Japanese patients than in the BIPARK I and II studies for OPC 25 mg, 50 mg, and placebo. 26 , 40 …”
Section: Opicapone Lifecycle: From Conception To Commercializationmentioning
confidence: 72%
See 1 more Smart Citation
“…The efficacy of adjunct opicapone in reducing OFF time in patients with motor fluctuations has been well established in phase 3 clinical trials, as well as in observational studies, and has been extensively reviewed elsewhere [73][74][75]. Three randomized, double-blind, placebo-controlled studies have examined the symptomatic effects of opicapone in PD patients with motor fluctuations, namely the BIPARK studies (I and II) [76,77] and, more recently, a phase 2b (COMFORT-PD) study conducted in the Japanese population [78]. Key findings from the separate studies are given in Table 1.…”
Section: Clinical Studies Of Opicapone In Patients With Wearing-offmentioning
confidence: 99%
“…Although previous studies have confirmed that the pharmacokinetic and pharmacodynamic profiles of opicapone are similar in Japanese and non-Japanese populations (Falcao et al 2016), there has been a lack of studies on the clinical efficacy and safety of opicapone in Japanese patients. Prior to this study, we conducted a double-blind, randomized, placebo-controlled study with opicapone tablets developed by Ono Pharmaceutical Co. Ltd. (Osaka, Japan) to evaluate the efficacy and safety of opicapone 25 mg and 50 mg tablets versus placebo in Japanese patients with PD and motor fluctuations despite treatment with an L-dopa and DCI combination (Takeda et al 2021). Results of this double-blind study found that, compared with placebo, both opicapone 25 mg and 50 mg tablets were associated with statistically significant reductions in OFF-time as well as improvements in other endpoints, including the percentage of ON-time responders and changes in total ON-time/ONtime without troublesome dyskinesia.…”
Section: Introductionmentioning
confidence: 99%